Women entrepreneurship in india in globalized economy - Rao, K. S.; Phani kumar, K. (university of Jaffna, 2014)
Indian women have to go a long way to achieve equal rights and position because traditions are deep rooted in Indian society where the sociological set up has been a male dominated one. Despite all the social hurdles, Indian women stand tall from the rest of the crowd ands are applauded for their achievements in their respective field. The transformation of social fabric of the Indian society, in terms of increased educational status of women and varied aspirations for better living, necessitated a change in the life style of Indian women. She has competed with man and successfully stood up with him in every walk of life and business is no exception for this. These women leaders are assertive, persuasive and willing to take risks, they managed to survive and succeed in this cut throat competition with their hard work, diligence and perseverance. Increasing numbers of women are becoming leaders of their own businesses, and many are struggling to achieve success. The present paper endeavors to study the concept of women entrepreneurs reasons women become entrepreneurs Reasons for slow progress of women entrepreneurs in India-suggestions for the growth of women entrepreneurs-schemes for promotion &development of women entrepreneurship in India.
Keywords: Entrepreneurship; Women; Business; Government; Problems; India